The Influence of the Principal's Transformational Leadership, Work Discipline, through Work Motivation on the Teacher Performance of Private Middle School in Banjarmasin City - Kii, Martina Ina; Suriansyah, Ahmad; Saleh, Muhammad (Formosa Journal of Applied Sciences, 2024)
This research aims to determine the influence of the principal's transformational leadership, work discipline, through work motivation on teacher performance. The research is quantitative with an ex post-facto research design conducted at private junior high schools in Banjarmasin City. The research population was 112 using a questionnaire. The research results show that there is a direct influence of the principal's transformational leadership on teacher performance of 0.411; the principal's transformational leadership on teacher work motivation is 0.51; work discipline on performance is 0.561; work discipline on work motivation is 0.442; work motivation on teacher performance is 0.275. Indirect influence of the principal's transformational leadership through work motivation on performance is 0.308; work discipline through work motivation on performance is 0.417.